Bedside assessment of cerebral perfusion reductions in patients with acute ischaemic stroke by near-infrared spectroscopy and indocyanine green. Issue 1 (5th January 2004) - Terborg, C; Bramer, S; Harscher, S; Simon, M; Witte, O W
Abstract : Objective: To detect perfusion reductions in patients with acute cerebral infarcts using near-infrared spectroscopy (NIRS) with indocyanine green (ICG) as tracer. Methods: Kinetics of an intravenous bolus of ICG were monitored by NIRS in 13 patients with acute infarction in the territory of the middle cerebral artery (mean (SD) age, 62.2 (13.0) years) and 12 controls (64.2 (9.1) years) at 2.8 (2.8) days after onset. NIRS optodes were placed bitemporally, with an interoptode distance of 4–5 cm. Absolute concentration changes in ICG were calculated. The following were assessed: time to peak, maximum ICG concentration, time interval between 0% and 100% maximum ICG concentration (interval), rise time (time between 10% and 90% ICG maximum), slope (maximum Δ ICG/interval), and blood flow index (BFI = maximum Δ ICG/rise time) of each hemisphere. Intraindividual differences were calculated between the two hemispheres. Results: Patients with ischaemic stroke had increased time to peak (p<0.01), interval (p<0.01), and rise time (p<0.01), while maximum ICG concentration (p<0.03), slope (p<0.01), and BFI (p<0.01) were diminished at the site of infarction compared with the unaffected hemisphere. In stroke patients, intraindividual differences in time to peak (p<0.001), interval (p<0.001), rise time (p = 0.001), maximum ICG concentration (p<0.02), slope (p<0.001), and BFI (p<0.001) were greater than in the controls, with excellent sensitivity and specificity for Δ time to peak (100% and 100%, respectively) and Δ time interval (100% and 91.7%). Conclusions: Measurement of interhemispheric differences in ICG kinetics by NIRS detects perfusion reductions in patients with acute middle cerebral artery infarction. This non-invasive bedside test is rapid, repeatable, without major side effects, and avoids transportation of critically ill patients.